Design and performance test of series underwater Savonius rotors with horizontal axis - Buana, Chandra; Tangko, Jumadi; Djalal, Muhammad Ruswandi; Lewi, Lewi; Ardaniah, Ardaniah; Mukhtaram, Nurrafii Al (International Journal of Applied Power Engineering (IJAPE), 2023)
The energy of river water flow or irrigation canals can be utilized by using a horizontal axis Savonius turbine, which converts low-speed river flow into electrical power with good design. The design of this turbine needs to pay attention to several parameters, namely, the deflector angle, the number of blades, the diameter and thickness of the blades, and the diameter and thickness of the end plates. However, the problem usually encountered is imperfect turbine construction due to the large drag force that occurs so that the power generated is low. Based on this background, it is proposed to manufacture and test the performance of a series Savonius underwater rotors with a horizontal axis. The research results found that the generator voltage without load was 25.6 V when the turbine only rotated at 47.2 rpm, whereas when under load, the average power produced was 8.5 watts with an average turbine speed of 31 rpm. The highest efficiency value on the rotor is 86.73%, with a torque value of 3.36 at a turbine speed of 29.9 rpm. This indicates that the tool can generate large torque at low speeds.